Possibilidade de desenvolvimento da oralidade por meio da transposição do gênero resenha para gênero videocast - Geizielle Nathália França Athouguia (2018)
The present research shows the importance of looking for alternatives to develop orality in the school environment. The present proposal makes use of the new information and communication technologies, including the cellular apparatus, in the Portuguese language classes, aiming to diversify the work with the textual genres. The objective of this research is to verify and analyze the possibility of developing orality through the transposition of the genre review for the videocast genre, through the process, in an intertextual way, that is, through the creation of new texts from other existing ones, as postulated by the National Curricular Parameters (1998). The methodology used consists of bibliographical review, questionnaire, focus group, application of a didactic sequence composed of the initial production (a video review), application workshops, creation of reviews, later transposition to the videocast and semi-structured interview. Considering this research, we have seen that the inclusion of new methodologies using different media in Portuguese language classes is able to attract students to work and think language as a form of expression of their ideas. This contributes to the acquisition of autonomy and security in the production of their texts, in a format different from the traditional, such as videocast, and a possibility of approach and development of oral-communicative competence through technology.